Performance and dementia : a cultural response to care - Hatton, Nicky (Basingstoke : Palgrave Macmillan, 2022)
This book explores how theatre and performance can change the way we think about dementia and some of the environments in which dementia care takes place.
K_B
Includes bibliographical references and index.
Keywords: Theater and older people; Dementia -- Patients -- Care -- Social aspects; People with mental disabilities and the performing arts